DEVELOPMENT OF MATHEMATICS LEARNING MEDIA CONCEPT BOARD (PAKELING BANDAR) FOR STUDENTS WITH SPECIAL NEEDS - Nurleha, Siti; Munfarikhatin, Anis; Meirista, Etriana (IJIET (International Journal of Indonesian Education and Teaching), 2024)
The research aims to produce mathematics learning media that is valid, practical, and effective according to the student’s needs, particularly in learning geometry for special needs students in Junior High School (phase D). The research method used is research and development with analysis flow; design, development, implementation, and evaluation. The study was conducted in a special school with a total of 3 students, namely 1 student with Autism Spectrum Disorder (ASD) and 2 students with intellectual disabilities. The data collection techniques used were questionnaires, observations, and test questions. The instruments used were validation questionnaires, teacher response questionnaires, student observation sheets, and sheets of pretest-posttest. The research results show that Pakeling Bandar media has valid criteria by the three validators with V-Aiken scores ≥0,61 in all aspects of the assessment. The practicality test obtained an average score of 3,59. Media Pakeling Bandar was declared very effective based on the assessment results post-test with a completion percentage of 98,33%. Moreover, learning media has met the criteria of being valid, practical, and effective and has met the needs of phase D ASD and mentally retarded students in maximizing the learning of geometric elements in the material around triangles, squares, and rectangles. With Pakeling Bandar media, students can understand the concept of the perimeter of plane figures, and calculate the perimeter of plane figures, and students are actively involved in learning in class.